Evidence That Aberrant Expression of Tissue Transglutaminase Promotes Stem Cell Characteristics in Mammary Epithelial Cells - Kumar, Anupam (Public Library of Science, 2011)
Cancer stem cells (CSCs) or tumor initiating cells (TICs) make up only a small fraction of total tumor cell population, but recent evidence suggests that they are responsible for tumor initiation and the maintenance of tumor growth. Whether CSCs/TICs originate from normal stem cells or result from the dedifferentiation of terminally differentiated cells remains unknown. Here we provide evidence that sustained expression of the proinflammatory protein tissue transglutaminase (TG2) confers stem cell like properties in non-transformed and transformed mammary epithelial cells. Sustained expression of TG2 was associated with increase in CD44(high)/CD24(low/-) subpopulation, increased ability of cells to form mammospheres, and acquisition of self-renewal ability. Mammospheres derived from TG2-transfected mammary epithelial cells (MCF10A) differentiated into complex secondary structures when grown in Matrigel cultures. Cells in these secondary structures differentiated into Muc1-positive (luminal marker) and integrin α6-positive (basal marker) cells in response to prolactin treatment. Highly aggressive MDA-231 and drug-resistant MCF-7/RT breast cancer cells, which express high basal levels of TG2, shared many traits with TG2-transfected MCF10A stem cells but unlike MCF10A-derived stem cells they failed to form the secondary structures and to differentiate into Muc1-positive luminal cells when grown in Matrigel culture. Downregulation of TG2 attenuated stem cell properties in both non-transformed and transformed mammary epithelial cells. Taken together, these results suggested a new function for TG2 and revealed a novel mechanism responsible for promoting the stem cell characteristics in adult mammary epithelial cells.